Water balance components estimation under scenarios of land cover change in the Vea catchment, West Africa. Issue 13 (2nd October 2020) - Larbi, Isaac; Obuobie, Emmanuel; Verhoef, Anne; Julich, Stefan; Feger, Karl-Henz; Bossa, Aymar Yaovi; Macdonald, David
ABSTRACT: The need for a detailed investigation of the Vea catchment water balance components cannot be overemphasized due to its accelerated land-cover dynamics and the associated impacts on the hydrological processes. This study assessed the possible consequences of land-use change scenarios (i.e. business as usual, BAU, and afforestation for the year 2025) compared to the 2016 baseline on the Vea catchment's water balance components using the Soil and Water Assessment Tool (SWAT) model. The data used include daily climate and discharge, soil and land use/land cover maps. The results indicate that the mean annual water yield may increase by 9.1% under the BAU scenario but decrease by 2.7% under the afforestation scenario; actual evapotranspiration would decrease under BAU but increase under afforestation; and groundwater recharge may increase under both scenarios but would be more pronounced under the afforestation scenario. These outcomes highlight the significance of land-cover dynamics in water resource management and planning at the catchment.